Cardioprotective Effect of Grape Seed Extract on Chronic Doxorubicin-Induced Cardiac Toxicity in Wistar Rats - Nasser Razmaraii; Hossein Babaei; Alireza Mohajjel Nayebi; Gholamreza Assadnassab; Javad Ashrafi Helan; Yadollah Azarmi (Tabriz University of Medical Sciences, 2016)
Purpose: The aim of the present study was to determine the ability of grape seed extract (GSE) as a powerful antioxidant in preventing adverse effect of doxorubicin (DOX) on heart function. Methods: Male rats were divided into three groups: control, DOX (2 mg/kg/48h, for 12 days) and GSE (100 mg/kg/24h, for 16 days) plus DOX. Left ventricular (LV) function and hemodynamic parameters were assessed using echocardiography, electrocardiography and a Millar pressure catheter. Histopathological analysis and in vitro antitumor activity were also evaluated. Results: DOX induced heart damage in rats through decreasing the left ventricular systolic and diastolic pressures, rate of rise/decrease of LV pressure, ejection fraction, fractional shortening and contractility index as demonstrated by echocardiography, electrocardiography and hemodynamic parameters relative to control group. Our data demonstrated that GSE treatment markedly attenuated DOX-induced toxicity, structural changes in myocardium and improved ventricular function. Additionally, GSE did not intervene with the antitumor effect of DOX. Conclusion: Collectively, the results suggest that GSE is potentially protective against DOX-induced toxicity in rat heart and maybe increase therapeutic index of DOX in human cancer treatment.